Development of Microbial Biofilms and Their Role in device, non-device and organ system level Infections - Liaqat, Farah; Ansar, Waiza; Muhammad, Noor; Tariq, Maria; Nazir, Zahid; Qamar, Hafiz Muhammad Ghuffran; Liaqat, Iram (BioScientific Review, 2025)
Background. Microorganisms, while providing many health benefits to human beings and other living organisms, are also responsible for significant infections. They cause infections in both planktonic and biofilm modes. Biofilms, defined as architectural communities of microorganisms encased in an extracellular polymeric substance (EPS), are strongly associated with infections. According to the National Institute of Health Sciences (NIH), biofilms account for 65% of microbial infections and 80% of chronic infections. Methods. This review examines the current literature on microbial biofilms, focusing on their formation stages, pathogenicity, resistance mechanisms, and associated infections. Data from various studies is analyzed to summarize biofilm development and its role in chronic infections. Results. Biofilm development involves four stages: attachment, microcolony formation, maturation, and dispersion. Quorum sensing (QS) mechanisms play a critical role in biofilm development and microbial communication. Biofilms enhance microbial pathogenicity and resistance to both the immune system and commercial antibiotics. They contribute to device-associated infections, such as those in catheters, and also to non-device infections in living tissues, as well as organ-level infections that impair systemic functions. Conclusion. A comprehensive understanding of microbial biofilms is essential for developing strategies to manage and control biofilm-associated infections. This review highlights the need for further research on the mechanisms of biofilm formation and resistance to improve infection prevention and treatment. Keywords: biofilm development, biofilm infections, chronic infections, device infections, microbial biofilms, non-device infections